Bullying in high school students of Los Olivos, Lima 2014 - Jaimes Velásquez, Carlos (2015)
Objectives: To determine the level of bullying in high school students in an educational institution in the district of Los Olivos. Method: descriptive and a quantitative approach. The population consisted of 101 students between 15-18 years of School “Alfredo Acosta Rebaza” located in the district of Los Olivos. The information was obtained through the survey technique called “This week in the classroom.” The analysis was performed using statistical tables and graphs, built in SPSS 20. Results: a low percentage of students present a level of bullying showing normal parameters. In comparing the level of bullying by gender, it is men who have higher rates of bullying. It was found that 15.3% of male students have suffered from aggressions more than once which leads to a low level of bullying, however only 3.9% of female students show a low incidence of bullying. Conclusions: There is a high level of bullying in the 4th and 5th year of secondary education in the School “Rebaza Alfredo Acosta” in the district of Los Olivos. In the study, levels of bullying are low, and noting that there is a low incidence rate of attacks or that may be prone to bullying.